Computer system for determination of hip joint contact stress distribution from antero-posterior pelvic radiograph - Iglič, Aleš (Radiology and oncology (Ljubljana), 1999)
Background. A computer system HIPSTRESS is described. The system can be used for the determination of the contact stress distribution in the hip joint for a known body weight and some characteristic pelvic and hip geometrical parameters which can be determined directly from the standard antero-posteriorradiograph. Conclusions. The system can be applied in clinicalpractice to predict an optimal stress distribution in different operative interventions in the hip.
Keywords: Biomechanics; Body weight; Hip joint; Radiographic image interpretation, computer-assisted; Radiography